Prehabilitative high-intensity interval training and resistance exercise in patients prior allogeneic stem cell transplantation - Kühl, Rea; Feyer, Jule; Limbach, Matthias; Pahl, Antonia; Stoelzel, Friederike; Beck, Heidrun; Wegner, Annika; Rosenberger, Friederike; Dreger, Peter; Luft, Thomas; Wiskemann, Joachim (Scientific reports, 2023)
Physical capacity prior allogeneic stem cell transplantation (allo-HCT) has been shown as a relevant prognostic factor for survival after transplant. Therefore, we evaluated feasibility and preliminary efficacy of a high-intensity interval training (HIIT) and moderate to high-intensity resistance exercise (RE) to increase physical capacity in patient’s prior allo-HCT. In this multicentre single arm pilot study, a supervised exercise program was performed twice weekly for 4-12 weeks prior allo-HCT, depending on the individual time remaining. Outcomes were feasibility (recruitment, adherence, safety), physical capacity (cardiorespiratory fitness [VO2peak], muscle strength) and patient reported outcomes (physical functioning, fatigue). Thirty patients were intended, 16 could be included, and 14 completed post intervention assessment (75% male, 55 ± 11 years). The study was stopped early due to a low recruitment rate. Nine patients (64%) reached the initial minimum planned number of eight exercise sessions. Individual adherence was high with 92% for HIIT and 85% for RE. 87% of all performed exercise sessions were completed without complaints and VO2peak increased significantly from 20.4 to 23.4 ml/kg/min. The low recruitment rate suggests that initiation of the intervention concept immediately before allo-HCT is feasible only in a small number of patients. In particular, the timeframe directly prior allo-HCT seems too short for exercise interventions, although the exercise program was designed to improve outcomes in a very short time frame. HIIT and RE were feasible, effective and well accepted by the included patients.